2023
DOI: 10.1093/plphys/kiad076
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the application of anti-CRISPR proteins in plants for tunable genome editing

Abstract: Anti-CRISPR proteins are very efficient for inhibiting CRISPR/Cas9-based genome editing tools in both herbaceous and woody plant species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…In addition, Liu and their team have shown that transient expression and stable transformation methods can be used to effectively activate AcrIIA4 and AcrIIA5 in herbaceous and woody plant species. The authors used leaf-infiltration and protoplast-based transient expression to investigate the effects of AcrIIA4 and AcrIA5 activities on the SpCas9-based adenine base editor (ABE7) in the herbaceous plants Arabidopsis (Arabidopsis thaliana) and N. benthamiana, as well as the woody plant hybrid poplar "717" (Populus tremula × P. alba hybrid clone INRA 717-1B4), and suggested that both AcrIIA4 and AcrIIA5 are capable of preventing target mutagenesis in the genome of N. benthamiana that is mediated by SpCas9/sgRNA (Liu et al, 2023).…”
Section: Type II Anti-crisprsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Liu and their team have shown that transient expression and stable transformation methods can be used to effectively activate AcrIIA4 and AcrIIA5 in herbaceous and woody plant species. The authors used leaf-infiltration and protoplast-based transient expression to investigate the effects of AcrIIA4 and AcrIA5 activities on the SpCas9-based adenine base editor (ABE7) in the herbaceous plants Arabidopsis (Arabidopsis thaliana) and N. benthamiana, as well as the woody plant hybrid poplar "717" (Populus tremula × P. alba hybrid clone INRA 717-1B4), and suggested that both AcrIIA4 and AcrIIA5 are capable of preventing target mutagenesis in the genome of N. benthamiana that is mediated by SpCas9/sgRNA (Liu et al, 2023).…”
Section: Type II Anti-crisprsmentioning
confidence: 99%
“…Acr proteins, in this light, are an underutilized regulatory mechanism in plant biotechnology. In both herbaceous and woody plant species, Acr proteins are effective at inhibiting CRISPR-Cas9based genome-editing tools (Liu et al, 2023). In this review, the numerous types of Acr proteins, their respective mechanisms of action, and the broad range of applications were discussed.…”
Section: Introductionmentioning
confidence: 99%